Landasan Etika Mahasiswa Dalam Menghadapi Tantangan Era Revolusi 4.0 - Septiliana, Lilla; Shaleh, Shaleh; Hidayati, Fina Hanifah (Jurnal Tarbiyah dan Ilmu Keguruan Borneo, 2024)
The Industrial Revolution 4.0 era brought significant changes in various aspects of life, including in the world of higher education. Students as agents of change are expected to have a strong ethical foundation to face the challenges they face in this era. This research aims to analyze the ethical foundation that students must have in facing the challenges of the Industrial Revolution Era 4.0. The research method used is literature study by collecting data from various sources such as scientific journals, books, articles and other related documents. The research results show that the ethical foundations of students who are effective in facing the challenges of the Industrial Revolution Era 4.0 include integrity, responsibility, social skills, adaptability, and technological awareness. Integrity refers to strong personal morality and ethics, responsibility involves taking a responsible attitude towards student duties and roles, social skills involve the ability to communicate and collaborate, adaptability involves the ability to adapt to technological changes, and technology awareness involves understanding the ethical implications of new technologies. This research provides a better understanding of the ethical foundations needed by students in facing the challenges of the Industrial Revolution Era 4.0.